The Influence of Clamshell on Mechanical Properties of Non-Structure Concrete as Artificial Reef (Asian Journal of Applied Sciences, 2017)
Clamshell waste had higher chemical content of Calcium Carbonate (CaCO3) than the limestone, egg shells, ceramic, or other materials. These physical properties gave the potential for material substitution as coarse aggregate in concrete artificial reefs. In addition, the utilization of leather waste in concrete structures could function as taxis for fish in the vicinity. This study utilized two types of coarse aggregate (filler) which were crushed stone and/or clamshell waste of the blood clamshells and kurkur clamshells. The test was to identify the mechanical properties of concrete artificial reef namely: Hammer test (ASTM C805), abrasion test (ASTM C779), the pressure test (SNI 03-1974-1990), split tensile test (ASTM C496 / C496M-11), Ultrasonic Pulse Velocity (UPV) test (ASTM C597-16), Porosity test (C642-13), permeability test (SN 505 252/1). The Concrete mixing is conducted according to SNI 03-2834-2000 standard and quality standard of solid concrete brick (SNI 03-0349-1989). Before the test, the concrete soaked in fresh water and sea water and left in the open air until 28 days. The results showed that the use of clamshell waste as filler had potential as a concrete compressive strength of non-structure approaches to the quality of solid concrete brick, as artificial reef material..Â